Improving satellite-based global rainfall erosivity estimates through merging with gauge data - Fenta, Ayele Almaw; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Yasuda, Hiroshi; Tsubo, Mitsuru; Borrelli, Pasquale; Kawai, Takayuki; Sewale Belay, Ashebir; Ebabu, Kindiye; Liyew Berihun, Mulatu; Sultan, Dagnenet; Asamin Setargie, Tadesaul; et al. (Journal of hydrology (Amsterdam), 2023)
•An integrated approach is proposed for mapping global rainfallerosivity.•GWR was used to integrate rainfall erosivity from satellite and gauge data.•Merging GPM-IMERG with GloREDa improved rainfall erosivity estimates.•Global mean annual rainfall erosivity was estimated to be 2020 MJ mm ha−1 h−1 yr−1.•A susceptibility map is proposed to identify regions prone to soil erosion by water. Rainfall erosivity is a key factor that influences soil erosion by water. Rain-gauge measurements are commonly used to estimate rainfall erosivity. However, long-term gauge records with sub-hourly resolutions are lacking in large parts of the world. Satellite observations provide spatially continuous estimates of rainfall, but they are subject to biases that affect estimates of rainfall erosivity. We employed a novel approach to map global rainfall erosivity based on a high-temporal-resolution (30-min), long-term (2001–2020) satellite-based precipitation product—the Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (GPM-IMERG)—and mean annual rainfall erosivity from the Global Rainfall Erosivity Database (GloREDa) stations (n = 3286). We used a residual-based merging scheme to integrate GPM-IMERG-based rainfall erosivity with GloREDa using Geographically Weighted Regression (GWR). The accuracy of the GWR-based merging scheme was evaluated with a 10-fold cross-validation against GloREDa stations. Based on GPM-IMERG-only, the global mean annual rainfall erosivity was estimated to be 1173 MJ mm ha−1 h−1 yr−1 with a standard deviation of 1736 MJ mm ha−1 h−1 yr−1. The mean value estimated via GPM-IMERG merged with GloREDa was 2020 MJ mm ha−1 h−1 yr−1 with a standard deviation of 3415 MJ mm ha−1 h−1 yr−1. Overall, GPM-IMERG-only estimates underestimated rainfall erosivity. The underestimations were greatest in areas of high rainfall erosivity. The accuracy of rainfall erosivity estimates from GPM-IMERG merged with GloREDa substantially improved (Nash-Sutcliffe efficiency = 0.83, percent bias = −2.4%, and root mean square error = 1122 MJ mm ha−1 h−1 yr−1) compared to estimates by GPM-IMERG-only (Nash-Sutcliffe efficiency = 0.51, percent bias = 27.8%, and root mean square error = 1730 MJ mm ha−1 h−1 yr−1). Improving satellite-based global rainfall erosivity estimates through integrating with gauge data is relevant as it can contribute to enhancing soil erosion modeling and, in turn, support land degradation neutrality programs.